A comparative study on efficacy and safety of glycopyrronium bromide + salmeterol/fluticasone and tiotropium bromide + salmeterol/fluticasone in chronic obstructive pulmonary disease - Deepak Kumar; A.K. Khare; Ram Babu Raman; Rahul Srivastava; Dibyadeb Ghosh (International Journal of Medical Research and Review, 2019)
Objective: To compare the effect of tiotropium bromide and glycopyrronium bromide in the treatment of chronic obstructive pulmonary disease.Methods: This was an open labeled Randomized controlled trial study. Patients diagnosed with COPD according to the Global Initiative for chronic Obstructive Lung Disease (GOLD) strategy were included in the study. The patients were divided in two groups and each group had 100 patients. Group A- COPD patients on Tiotropium bromide + Salmeterol/Fluticasone; Group B – COPD patient on Glycopyrronium bromide + Salmeterol/Fluticasone. Tiotropium bromide: 18 mcg OD, Glycopyrronium bromide: 50 mcg OD along with Salmeterol 50 mcg/Fluticasone 100mcg was given.Results: The mean age of patients of Group A and Group B was 56.28±7.78 and 57.64±8.06 years respectively. Baseline variables were comparable between the groups. There was significant (p<0.05) difference in PFT parameters between the groups at 12 and 24 weeks except for FEV1/FVC. The mean change was higher in Group B compared to Group A from 0 week to 24 weeks. There was clinical improvement among all the patients in both the groups.Conclusion: Once-daily GLY demonstrated similar effects to TIO when combined with SAL/FP in patients with moderate and severe COPD.